Writer's Digest grammar desk reference : the definitive source for clear and correct writing - Lutz, Gary, 1955- (Writers Digest Books, 2010)
Presents a guide to grammar, punctuation, capitalization, and abbreviations, and contains a glossary of commonly misused words.